2008
DOI: 10.1002/mds.22045
|View full text |Cite
|
Sign up to set email alerts
|

Variations in gender ratios support the connection between smoking and Parkinson's disease

Abstract: Smokers have a decreased risk of Parkinson's disease (PD), but this association could simply be the result of a common factor causing both PD and aversion to smoking. Smoking behavior in industrialized nations has changed dramatically over the second half of the 20th century, with diverging patterns in male and female smoking rates. We therefore examined whether PD incidence changed concomitantly, as would be expected if smoking truly reduced PD risk. We performed a PUBMED search to identify relevant studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…When no individual-level data are available, this study design is less informative compared to a casecontrol or a cohort study. Nevertheless, the authors reported that with increasing proportion of women who smoke in a country, the incidence of PD in women relative to that in men declined, an expected finding in the presence of a causal relationship [450].…”
Section: Suggested Systemic Biases In Studies Of Smoking and Pdmentioning
confidence: 95%
See 1 more Smart Citation
“…When no individual-level data are available, this study design is less informative compared to a casecontrol or a cohort study. Nevertheless, the authors reported that with increasing proportion of women who smoke in a country, the incidence of PD in women relative to that in men declined, an expected finding in the presence of a causal relationship [450].…”
Section: Suggested Systemic Biases In Studies Of Smoking and Pdmentioning
confidence: 95%
“…Another approach to study the relationship between smoking and PD was taken in an ecologic study [450] that examined the male to female ratio in PD incidence in different countries and compared these ratios with the corresponding male to female ratios of smoking. When no individual-level data are available, this study design is less informative compared to a casecontrol or a cohort study.…”
Section: Suggested Systemic Biases In Studies Of Smoking and Pdmentioning
confidence: 99%
“…Over a half-century of studies show overwhelmingly that smoking is inversely associated with Parkinson's disease (Morens et al, 1995;Gorell et al, 1999;Hernán et al, 2001;Allam et al, 2004;Alves et al, 2004;Ritz et al, 2007;Thacker et al, 2007;Elbaz and Moisan, 2008;Morozova et al, 2008;Chen et al, 2010;Ritz and Rhodes, 2010) and other Lewy body-related pathologic conditions (Tsuang et al, 2010). A prime question is whether this decreased incidence of Parkinson's disease in those with a history of smoking is due to the increased mortality risk associated with smoking.…”
Section: A Epidemiological Studies and Smokingmentioning
confidence: 99%
“…Interestingly, one of most consistently observed associations with PD is the inverse association between (personal) smoking and PD (48)(49)(50)(51)(52). Among participants who smoke themselves, the risk of PD is approximately half of that in non-smokers (49,50).…”
Section: Second-hand (Passive) Smokingmentioning
confidence: 99%
“…The exact cause of neuronal depletion is unknown, but it may involve mitochondrial dysfunction (3), inflammatory reactions and oxidative stress (4). Exposure to pesticides (5), herbicides (6) and heavy metals (7) were shown to increase PD risk, whereas smoking (8)(9)(10), use of non-steroidal anti-inflammatory drugs (NSAIDs) (11), consumption of caffeine and high urate (12) are considered as protective factors.…”
Section: Introductionmentioning
confidence: 99%